One-Time Acute Heat Treatment Is Effective for Attenuation of the Exaggerated Exercise Pressor Reflex in Rats With Femoral Artery Occlusion - Qin, Lu; Li, Jianhua (Frontiers in Physiology, 2020)
The purpose of this study was to determine the effects of one-time acute heat treatment (HT) on the exaggerated exercise pressor reflex in a model of peripheral arterial insufficiency induced by ligation of the femoral artery and to further examine the underlying mechanism of ATP-P2X3 signal activity during this process. The blood pressure (BP) response to static muscle contraction and muscle tendon stretch was recorded to determine the exercise pressor reflex. Also, αβ-methylene ATP (αβ-me ATP) was injected into the arterial blood supply of the hindlimb muscles to stimulate P2X3 receptors in the muscle afferent nerves. To process one-time acute HT, a heating pad was placed locally on the hindlimb and the muscle temperature (Tm) was increased by ~1.5 °C and maintained for 5 min. Compared with control rats, a greater mean arterial pressure (MAP) response to muscle contraction was observed in rats with femoral occlusion in a pre-heat control session (28±2 mmHg in occluded rats/n=12 vs. 18±2 mmHg in control rats/n=9; P<0.05). The one-time acute HT attenuated the amplification of the BP response in rats with femoral artery occlusion (MAP response: 19±8 mmHg in occluded rats + HT/n=11; P<0.05 vs. occluded rats). In contrast, HT did not significantly attenuate amplification of MAP response to muscle stretch and αβ-me ATP injection in rats with femoral artery occlusion and controls (all P>0.05). Our data suggest that one-time acute HT selectively attenuates the amplified pressor response induced by activation of the metabolic and mechanical components of the reflex in rats after femoral artery occlusion. The suppressing effects of acute HT on the exaggerated exercise pressor reflex are likely mediated through a reduction in metabolites (e.g. ATP) stimulating the muscle afferent nerves in contracting muscle, but unlikely through direct alteration of P2X receptors per se.